1988
DOI: 10.1002/clc.4960110604
|View full text |Cite
|
Sign up to set email alerts
|

One‐year death rate in 270 patients with suspected acute myocardial infarction, initially treated with intravenous magnesium or placebo

Abstract: Summary:In a double-blind, placebo-controlled study, 273 patients with suspected acute myocardial infarction (AMI) were randomized to receive either 48-h magnesium (Mg) or placebo therapy intravenously, initiated immediately on admission to hospital. We describe the results from a 1-year survey in 270 of the patients, who were available for follow-up. Patients were equally divided: 135 received Mg and 135 received placebo. Mg treatment was associated with a marked reduction in 1-year death rate from 32% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Our results are concordant with Rasmussen et al [29]who reported on a one-year death rate in 270 patients with suspected AMI, initially treated with intravenous magnesium or placebo. All-cause mortality was 20% in patients who received magnesium, compared with 32% in patients who received placebo (p = 0.018), and mortality from ischemic heart disease was 15% compared with 28% (p = 0.006), respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are concordant with Rasmussen et al [29]who reported on a one-year death rate in 270 patients with suspected AMI, initially treated with intravenous magnesium or placebo. All-cause mortality was 20% in patients who received magnesium, compared with 32% in patients who received placebo (p = 0.018), and mortality from ischemic heart disease was 15% compared with 28% (p = 0.006), respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Our study not only confirms the findings of Rasmussen et al [29]who state that the beneficial effect of magnesium on mortality in a high-risk population (patients ineligible for thrombolysis and the elderly) is mainly during the first month after AMI, but continues to demonstrate an extended beneficial effect up to 4.8 years after AMI, concomitantly with a higher LVEF. However, it should be noted that the added beneficial effects of intravenous magnesium therapy observed in the current study could also be due to statistical bias or chance.…”
Section: Discussionsupporting
confidence: 80%
“…Five of them (Abraham et al, 1987;Ceremuzynski et al, 1989;Rasmussen et al, 1986Rasmussen et al, , 1987Rasmussen et al, , 1988aSchechter et al, 1990;Smith et al, 1986) reported a reduction in mortality, in frequency of arrhythmias or both in those patients who received magnesium. Two (Feldstedt et al, 1988;Morton et al, 1984) were negative; the first of these included only 76 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two (Feldstedt et al, 1988;Morton et al, 1984) were negative; the first of these included only 76 patients. Rasmussen et al (1986Rasmussen et al ( , 1988a randomised 273 patients with suspected acute myocardial infarction to receive 62 mmol magnesium chloride or saline over 48 h. Significantly fewer patients had infarction confirmed in the magnesium group and mortality at 1 year was 32% in the placebo group and 20% in the magnesium group (P < 0.02). Although none of the trials had sufficient statistical power to be conclusive, collectively they strongly suggest a beneficial effect of intravenous magnesium and this interpretation is supported by a formal metaanalysis of all the available data (Teo et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies show the advantage of Mg 2+ therapy in coronary artery disease. For coronary artery disease, at least ten prospective, randomized, double‐blind, controlled trials report supportive results comparing Mg 2+ supplementation with placebo 28–34 . These studies have demonstrated a decrease in myocardial damage and reduced mortality rate in subsets of high‐risk patients when Mg 2+ therapy was administered before reperfusion occurred.…”
Section: Discussionmentioning
confidence: 96%